(untitled) (Journal of Engineering, 2010)
An experimental system was designed and built to produce the flash evaporation of upward water flow in a (1.8 m) vertical mounted glass test section pipe. The water loses the static head as it moves up, accordingly flash evaporation occurs somewhere inside the test section, where the water local temperature reaches its saturation temperature at that position, which is dependent on the water inlet temperature and its mass flow rate. The steam quality in the test section exit was measured by collecting the steam generated in the test section outlet and condensed in the condenser at specified time. The hydrogen bubbles are injected inside the two-phase mixture flow within the test section. These bubbles act as an exciter for steam generation inside saturated water. Water electrolysis using (12 V) and ionization current (7 A), increases steam quality at test section outlet by (33%) when it is compared to that obtained without water electrolysis. A reduction of (42%) in non-equilibrium temperature difference is achieved using the same ionization settings. The effect of ionization process on flash inception point and temperature is investigated from the experiments.The experimental results are compared to the theoretical results obtained using mathematical model based on solving the mass, momentum and energy equations for two-phase flow assuming separated flow model.The effect of the electrical power used for water ionization is simply simulated in these calculations using mass and heat balance equation that covers the boundary conditions of the system.